2016
DOI: 10.1016/j.immuni.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Yolk Sac Macrophages, Fetal Liver, and Adult Monocytes Can Colonize an Empty Niche and Develop into Functional Tissue-Resident Macrophages

Abstract: Tissue-resident macrophages can derive from yolk sac macrophages (YS-Macs), fetal liver monocytes (FL-MOs), or adult bone-marrow monocytes (BM-MOs). The relative capacity of these precursors to colonize a niche, self-maintain, and perform tissue-specific functions is unknown. We simultaneously transferred traceable YS-Macs, FL-MOs, and BM-MOs into the empty alveolar macrophage (AM) niche of neonatal Csf2rb(-/-) mice. All subsets produced AMs, but in competition preferential outgrowth of FL-MOs was observed, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
422
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 517 publications
(455 citation statements)
references
References 37 publications
29
422
2
2
Order By: Relevance
“…We therefore investigated the concentration of IL-33 protein in lysed lung cells in steady state (PBS) or after administration of HDM to unsensitized mice. In steady state, IL-33 protein concentration peaked around PND14 ( Figure 4C; van de Laar et al, 2016). At 16 hr after the administration of HDM, the expression of IL-33 was significantly higher in lung cell homogenates of PND14 lungs compared to PND3 or adult lungs ( Figure 4C).…”
Section: Il-33 Blockade Inhibits Neonatal Type 2 Immunity and Enhancementioning
confidence: 93%
See 2 more Smart Citations
“…We therefore investigated the concentration of IL-33 protein in lysed lung cells in steady state (PBS) or after administration of HDM to unsensitized mice. In steady state, IL-33 protein concentration peaked around PND14 ( Figure 4C; van de Laar et al, 2016). At 16 hr after the administration of HDM, the expression of IL-33 was significantly higher in lung cell homogenates of PND14 lungs compared to PND3 or adult lungs ( Figure 4C).…”
Section: Il-33 Blockade Inhibits Neonatal Type 2 Immunity and Enhancementioning
confidence: 93%
“…This alveolar phase of lung growth lasts until 3 years of age and is controlled by many growth factors and cytokines that could also influence (Schittny et al, 2008). Fetal lung is first populated around E12 by CD45 + yolk sac-derived macrophages (De Kleer et al, 2014;Guilliams et al, 2013;Schulz et al, 2012;van de Laar et al, 2016). We recently have shown that this first wave of yolk sac-derived macrophages is followed by a consecutive wave of fetal liver-derived monocytes that enter the lung around E18, the start of the saccular phase in mice, and give rise to alveolar macrophages (AM) under the influence of GM-CSF van de Laar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is a large body of evidence that AIHA can be induced by an underlying disease in the patient which may lower the threshold of the neutrophils to phagocytose IgG-opsonized RBCs, and thus exacerbate the hemolytic anemia. It is important to keep in mind that during these pathological conditions the cellular composition of the spleen can change 43,44 which subsequently may influence phagocytosis. Additionally, IV immunoglobulin administration, a common therapy in AIHA can change cellular distribution in the spleen which may affect erythrophagocytosis.…”
Section: Inf Interferonmentioning
confidence: 99%
“…5C). It should be noted that this protective effect was unexpected, because macrophages transferred into the lung, regardless of their origin, rapidly (within days) alter their phenotype (33,34). Overall, based on depletion (Fig.…”
Section: Vim (A) Im (B) Am (C)mentioning
confidence: 85%